Literature Review of Determinants of Entrepreneurial Interest Among Generation Z - Rizki Asrulloh; St Maryam (Indonesian Development Economics and Localities, 2025)
This study aims to analyze the factors that influence entrepreneurial interest among Generation Z, especially in the context of higher education. Generation Z is known as a digital generation that has unique characteristics, such as high-tech skills, multitasking, and an orientation towards speed and efficiency. This study focuses on five main factors that are considered to have a significant influence on entrepreneurial interest, namely personality, entrepreneurial education, peers, entrepreneurial mentality, and entrepreneurial knowledge. The method used is quantitative descriptive with a literature study approach and previous research results. The results of the study indicate that internal factors such as personality and mentality have a significant influence on entrepreneurial interest, supported by external factors such as peer environment and entrepreneurial education. This study recommends strengthening integrative entrepreneurial education and positive social support to foster an entrepreneurial spirit in Generation Z.